A tomographic image of the fault zone on the north anatolian fault - Afacan Ergün, Tuğçe. (Thesis (M.S.) - Bogazici University. Kandilli Observatory and Earthquake Research Institute, 2006., 2006)
During the fall of 2003, seismic data were collected in the eastern Marmara Region on the North Anatolian Fault Zone near izmit rupture zone by a controlled source experiment. The fault was clearly exposed on the surface and the thickness of the sediments in the basin is expected to be greater than several hundred meters. The data were acquired along a 1.2 km long nmih-south profile with a total of 50 recorders equipped with 4.5 Hz geophones. 3-component geophones were used near the fault zone to detect trapped waves. The shot spacing was 5 m and receiver spacing was varying from 1Om to 20m. More than 180 shots were fired using a vibroseis. Data were recorded continuously with 1OOHz sampling rate. . This study is a step towards a determination of a shallow P wave velocity structure on the NAFZ near izmit rupture. We applied regularized inversion technique to the first arrival travel times. More than 6500 picks from 129 shot-gathers were used in the analysis. A shallow P wave velocity image (<200m) from travel time tomography was obtained in the izmit basin. The results indicate a fault zone of approximately 100 m thick. A velocity contrast was detected between the fault zone and surrounding blocks. The P wave velocity on the southern block varies between a range 1.4 - 1. 7 km/s and 1. 7 - 2.0 km/s on the northern block the velocity decreases to 1.4 km/s within the fault zone. 3-component recordings and fan shots indicates the presence of the fault zone consistent with the . tomographic image. Previous seismological studies in the region also show that the thickness of the fault zone is on the order of approximately 1OOm.
Keywords: Earthquake prediction -- Turkey.; Seismology -- Turkey.